Tindak Tutur Pelaku Pencemaran Nama Baik Luhut Binsar Panjaitan Oleh Haris Azhar Dan Fatia Maulidiyanti Dalam Konten Sosial Media Youtube ‘Ada Lord Luhut Dibalik Relasi Ekonomi-Ops Militer Intan Jaya’ - Annisa Pratiwi; Fatiya Cahya; Leony Silitonga (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the speech acts of defamation perpetrators on YouTube social media carried out by Haris Azhar and Fatia Maulidiyanti towards Luhut Binsar Panjaitan. The method used in this research is descriptive qualitative to see how the language used by speakers in YouTube social media content entitled 'There is Lord Luhut behind the Intan Jaya Military Economic-OPS Relations' in pragmatic studies. Data collection was carried out using the note-taking method and then classifying the types of speech acts produced. The results of the research showed that there were 10 data which included 1 declarative illocutionary speech act, 5 representative illocutionary speech acts, 2 locutionary speech acts, and 2 expressive illocutionary speech acts.